A history of technology (Clarendon Press, 1979)
Contents: Part I. Basic social factors; Part II. Food-Collecting stage; Part III. Domestic activities; Part IV. Specializing industries; Part V. Utilization of metals; Part VI. Transport; Part VII. The preparation for science